Acute psychotic disorder associated with immunosuppressive agent use after renal transplantation: a case report - Fulya Gok; Meliha Zengin Eroglu (Psychiatry and Clinical Psychopharmacology, 2017)
Kidney transplantation is the best treatment option for end-stage renal disease in appropriate patients. Immunosuppressant agents given in this duration can cause many psychiatric disorders. In this paper, we present a young kidney transplant patient with psychosis constituted delusions about his transplanted kidney after 4 years later from transplantation. He had refused to take his immunosuppressant pills because of psychotic process. In this paper, we wanted to discuss the psychiatric risks of immunosuppressant agents and importance of the psychiatric treatment in this aspect.